Biopsychosocial-Based Exercise Model for Rheumatic Diseases Via Telerehabilitation: A Case Series with a One Year Follow Up - Nacar, Nazli Elif; Karaca, Nur Banu; Bulut, Zeynep Irem; Sari, Erkin Oguz; Bulut, Senem; Yakut, Yavuz; Unal, Edibe (Nova Southeastern Univ, 2025)
Purpose: This study aims to examine the sustainability of the biopsychosocial exercise performed by telerehabilitation on individuals with rheumatic disease, with and without supervision, and investigate the effect of the biopsychosocial-based exercise model on biopsychosocial status, general health status, and anxiety-depression levels of individuals. Method: Twenty patients with rheumatic diseases performed a biopsychosocial-based exercise model Cognitive Exercise Therapy Approach via telerehabilitation with physiotherapist-supervised and unsupervised exercises who continued for three sessions per week for 12 months. Outcome measures were Health Assessment Questionnaire, Hospital Anxiety and Depression Scale, and Cognitive Exercise Therapy Approach-Biopsychosocial Questionnaire. Patients were assessed at baseline, 3rd, 6th, 9th, and 12th months. Results: There was no significant difference by time for Health Assessment Questionnaire (p=0.512) and Hospital Anxiety and Depression Scale-anxiety and depression scores (p=0.162 and p=0.825, respectively) between the five measures at the one-year followup. Similarly, there is no significant difference in Cognitive Exercise Therapy Approach-Biopsychosocial Questionnaire score outcomes by time (p=0.184). Conclusion: In this study a group of rheumatic patients with face-to-face biopsychosocial exercise habits were able to maintain their exercise habits with realtime telerehabilitation with or without supervised during the 1-year follow-up period during the COVID-19 pandemic was shown. Although there was no improvement in the parameters during the pandemic period when social isolation and depression-anxiety disorders increased, the level of recovery which individuals had previously gained was not adversely affected and the healing properties were preserved with the help of telerehabilitation.
Keywords: Telerehabilitation; exercise; rehabilitation; rheumatology; anxiety